Pendampingan Ibu Rumah Tangga dalam Pemanfaatan Pekarangan dengan Tanaman Warung Hidup di Dukuh Mardirejo, Kalikebo - Piscolia Dynamurti Wintoro; Wiwin Rohmawati; Liawati (WASATHON Jurnal Pengabdian Masyarakat, 2023)
Based on the results of observations in Kalikebo Village, Trucuk District, residents generally have a fairly large yard. A large yard like this can be used as a living stall for daily needs while at the same time meeting the nutritional needs of family members, expectant mothers, pregnant women and for making complementary foods. Currently the yard is still not being utilized optimally by the residents because of the lack of knowledge of the residents, especially knowledge in the health sector. This situation is due to the relatively low education of mothers so that the ability to develop themselves to improve family health is still low. While the results of the preliminary study obtained data as much as 10-14% of toddlers in Kalikebo Village were stunted. The aim of this activity is to empower housewives in utilizing their yards by planting living stalls (vegetables and fruit) which contain lots of iron, folic acid and iodine which can prevent stunting from occurring. The target in this community service activity is representatives of housewives in 4 RTs in the Kalikebo Village area, namely 150 people. The method used in this community service activity is assistance, counseling and demonstrations in utilizing the yard. The results that have been achieved in this activity are that the women participating in the assistance have understood stunting and a living stall and a living stall has been formed in Mardirejo Hamlet, Kalikebo Village.